Why Does Population Aging Matter So Much for Asia? Population Aging, Economic Growth, and Economic Security in Asia - Sang-Hyop Lee; Andrew Mason; Donghyun Park (Asian Development Bank (ADB), 2011)
Asia as a whole is experiencing a rapid demographic transition toward older populations, though different countries are at different stages of this region- wide trend. We document Asia's aging population, describe the region's old-age support systems, and highlight the regional socioeconomic implications of the transition for those support systems. Aging populations present two fundamental challenges to Asian policymakers: (1) developing socioeconomic systems that can provide economic security to growing numbers of elderly while (2) sustaining strong economic growth over the next few decades. Successfully addressing these two challenges will be vital for ensuring Asia's continued economic success in the medium and long term.
hdl:11540/2000
Keywords: 330; Alternde Bevölkerung; Altersvorsorge; Wirtschaftswachstum; Asien